Development of desmos application integrated ethnomathematics on geometry for grade IV UPT SDN 101826 Tuntungan - Frida Marta Argareta Simorangkir; Lolly Jean C. Simbulas; Ferry Indra Sakti H. Sinaga (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
Ulos, as one of the traditional fabrics of Batak Toba, can be used as a learning resource, especially for geometry. Every motif and colour on ulos has particular meanings and messages related to beliefs, myths, history, and Batak cultural values. Need help from Desmos to visualise the geometric concepts found in ulos. This research aims to develop a learning media using the Desmos application integrated with Ethnomathematics-Ulos to enhance mathematical literacy. The research method used is Research and Development with the ADDIE model. The research instrument uses a rating scale and an essay test. The results of developing material and language on geometry obtained a percentage of 93,69% with a very valid feasibility category. The results of product validation by practitioners as media experts got a very valid category with a rate of eligibility of 91,91%. Moreover, the teacher evaluation results got an efficient category with a percentage of 92,88%. The N-Gain value is 0,80 > 0,7, in the “High” category, meaning that the learning media effectively improve students' mathematical literacy skills.